Formulation and Evaluation of mucoadhesive microsphere of montelukast for nasal delivery - Singh, Shivanshu; Pandey, Jaideo (Journal of Neonatal Surgery, 2025)
Mucoadhesive drug delivery systems are drug delivery techniques that enable extended, intimate contact between the medication and the mucosa. The goal of the current study was to create mucoadhesive microspheres for nasal administration in order to enhance therapeutic efficacy, prolong residence duration, and avoid hepatic first-pass metabolism. In our study, we created Montelukast mucoadhesive microspheres with chitosan conjugation using the Emulsification cross linking technique. The stability, in vitro drug release, in vitro mucoadhesion, percentage yield, particle size, entrapment efficiency, and swelling’s property of the microspheres were evaluated. Microspheres were characterized using infrared spectroscopy and scanning electron microscopy. The average microsphere particle size in each batch was between 10 and 50 µm, guaranteeing that each batch had the right handling characteristics. For all formulations, the range of drug encapsulation efficiency was found to be 75.71% to 89.24%. The percentage-yield of the drug for each formulation was found to vary between 86.51% and 91.58%. The observed mucoadhesion percentages ranged from 62.17% to 73.45%. All of the formulations demonstrated controlled drug release for up to six hours when evaluated for drug release in vitro using phosphate’s buffer pH 6.8. As per the collected data, mucoadhesive microsphere preparation techniques are a very promising nasal administration method that can enhance patient adherence and provide medicine over a longer duration